Host–Guest Complexation of Perethylated Pillar[5]arene with Alkanes in the Crystal State. Issue 34 (1st July 2015) - Ogoshi, Tomoki; Sueto, Ryuta; Yoshikoshi, Kumiko; Sakata, Yoko; Akine, Shigehisa; Yamagishi, Tada‐aki
Abstract: Activated perethylated pillar[5]arene crystals show an unexpected alkane‐shape‐ and ‐length‐selective gate‐opening behavior. Activated crystals were obtained upon removing solvents from perethylated pillar[5]arene crystals by heating. The activated crystals could quantitatively take up n ‐alkanes with carbon chains containing more than five carbon atoms as a consequence of their gate‐opening pressure. As the chain length of the n ‐alkanes increased, the gate pressure decreased. A transformation into a herringbone structure was induced when n ‐hexane was used as a guest. By contrast, cyclic and branched alkanes were not taken up and could not induce a crystal transformation because they were too large to fit in the cavities of the pillar[5]arene. Alkane‐shape‐selective molecular recognition of pillar[5]arenes in the solution state was translated into the vapor/crystal state. Abstract : Gate crashers : Activated perethylated pillar[5]arene crystals have been demonstrated to show selective gate‐opening behavior depending on alkane shape and length. The activated crystals could quantitatively take up n ‐alkanes with more than five carbon atoms, and n ‐hexane could even be stored under reduced pressure. In contrast, the gate‐opening behavior was not observed in the adsorption of cyclic and branched alkanes.